Cu2+1O/graphene nanosheets supported on three dimensional copper foam for sensitive and efficient non-enzymatic detection of glucose. Issue 31 (31st March 2017) - Yang, Liang; Liu, Daoping; Cui, Guomin; Xie, Yingming
Abstract : Three dimensional copper foam/Cu2+1 O/graphene nanosheets for sensitive and efficient non-enzymatic detection of glucose. Abstract : In situ growth of Cu2+1 O (Cu2 O with metal excess defects) was achieved through a facile hydrothermal process by employing porous Cu foam (CF) as substrate and the precursor, meanwhile, graphene nanosheets (GN) were deposited onto the Cu2+1 O/Cu foam substrate. The GN/Cu2+1 O/CF hybrid electrode provides a large accessible surface area, and contact between GN/Cu2+1 O and current collector (Cu foam) with good conductivity facilitated electron/ion transport. When being used as a potential biosensor for nonenzyme glucose detection, cyclic voltammetry (CV) and amperometric electrochemical method to evaluate the electrocatalytic performance of GN/Cu2+1 O/CF, and the GN/Cu2+1 O/CF hybrid electrode exhibits multistage linear detection ranges with high sensitivity (3.076 mA mM −1 cm −2 ) and the detection limit is 5 μM. Furthermore, the GN/Cu2+1 O/CF electrode also presented excellent repeatability, stability and reproducibility and selectivity. The design of GN/Cu2+1 O/CF hybrid electrode provided a useful strategy for design electrochemistry non-enzymatic biosensors.